QUBIC III: Laboratory characterization. Issue 4 (1st April 2022) - ,; Torchinsky, S.A.; Hamilton, J.-Ch.; Piat, M.; Battistelli, E.S.; de Bernardis, P.; Chapron, C.; D'Alessandro, G.; De Petris, M.; Gamboa Lerena, M.M.; González, M.; Grandsire, L.; et al.
Abstract: We report on an extensive test campaign of a prototype version of the QUBIC (Q & U Bolometric Interferometer for Cosmology) instrument, carried out at Astroparticle Physics and Cosmology (APC) in Paris. Exploiting the novel concept called bolometric interferometry, QUBIC is designed to measure the CMB polarization at 150 and 220 GHz from a high altitude site at Alto Chorillo, Argentina. The prototype model called QUBIC Technological Demonstrator (QUBIC-TD) operates in a single frequency band (150 GHz) and with a reduced number of baselines, but it contains all the elements of the QUBIC instrument in its final configuration. The test campaign included measurements of the synthesized beam and of the polarization performance, as well as a verification of the interference fringe pattern. A modulated, frequency-tunable millimetre-wave source was placed in the telescope far-field and was used to simulate a point source. The QUBIC-TD field of view was scanned across the source to produce beam maps. Our measurements confirm the frequency-dependent behaviour of the beam profile, which gives QUBIC the possibility to do spectral imaging. The measured polarization performance indicates a cross-polarization leakage less than 0.6%. We also successfully tested the polarization modulation system, which is provided by a rotating half wave plate. We demonstrate the full mapmaking pipeline using data from this measurement campaign, effectively giving an end-to-end checkout of the entire QUBIC system, including all hardware subsystems, their interfaces, and the software to operate the whole system and run the analysis. Our results confirm the viability of bolometric interferometry for measurements of the CMB polarization.